Antagonist G-targeted liposomes for improved delivery of anticancer drugs in small cell lung carcinoma - Carvalheiro, Manuela (2022)
FCT_UID/Multi/00612/2019. FCT_UIDB/00100/2020. FCT_UIDP/00100/2020.